The Chromophore Structures of the Pr States in Plant and Bacterial Phytochromes - Murgida, Daniel Horacio (2007)
The resonance Raman spectra of the Pr state of the N-terminal 65-kDa fragment of plant phytochrome phyA have been measured and analyzed in terms of the configuration and conformation of the tetrapyrroles methine bridges. Spectra were obtained from phyA adducts reconstituted with the natural chromophore phytochromobilin as well as phycocyanobilin and its isotopomers labeled at the terminal methine bridges through C-13/C-12 and D/H substitution. Upon comparing the resonance Raman spectra of the various phyA adducts, it was possible to identify the bands that originate from normal modes dominated by the stretching coordinates of the terminal methine bridges A-B and C-D. Quantum chemical calculations of the isolated tetrapyrroles reveal that these modes are sensitive indicators for the methine bridge configuration and conformation. For all phyA adducts, the experimental spectra of Pr including this marker band region are well reproduced by the calculated spectra obtained for the ZZZasa configuration. In contrast, there are substantial discrepancies between the experimental spectra and the spectra calculated for the ZZZssa configuration, which has been previously shown to be the chromophore geometry in the Pr state of the bacterial, biliverdin-binding phytochrome from Deinococcus radiodurans (Wagner, J. R., J. S. Brunzelle, K. T. Forest, R. D. Vierstra. 2005. Nature. 438: 325-331). The results of this work, therefore, suggest that plant and bacterial (biliverdin-binding) phytochromes exhibit different structures in the parent state although the mechanism of the photoinduced reaction cycle may be quite similar.